A lambda/plasmid Cre/lox hybrid vector for large genomic (18kb) fragment insertions and fungal genomic library construction - Joseph P. Brunelli; Martin L. Pall (Fungal Genetics Reports, 1995)
We have previously constructed lambda/plasmid hybrid vectors designed for both fungal cDNA and genomic library construction (Brunelli and Pall, 1994 Fungal Genet. Newslet. 41:63-65). The genomic library inserts, however, were limited to about 11 kb in size due to the size limitations of lambda packaging. We have constructed a similar vector that has three advantages over these earlier hybrid vectors, as discussed further below. The plasmid pBARGEM7-2 (Pall and Brunelli, 1993. Fungal Genet. Newslet. 40:59-61) was modified by inserting a stuffer sequence into the BamHI site of the polylinker. The stuffer sequence was about 6 kb and can be cut out with BamHI, yielding two BamHI fragments of about 4.5 kb and 1.5 kb. The 4.5 kb fragment contains the lacZ gene, producing very blue colonies (or plaques in lambda) on Xgal medium.